2017
DOI: 10.1002/bmc.3934
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetic study of the main components of cortex fraxini after oral administration in normal and hyperuricemic rats

Abstract: Cortex Fraxini is an important traditional Chinese herbal medicine used for the treatment of gout and hyperuricemia. An efficient and rapid ultra-performance liquid chromatography mass spectrometry method was developed and validated for simultaneous quantitation of six coumarins (aesculin, fraxin, aesculetin, fraxetin, sopoletin and 7-hydroxycoumarin) in normal and hyperuricemic rats plasma after oral administration of Cortex Fraxini. The method could successfully be applied for pharmacokinetics studies. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…It should be noted that there was a progressive decrease in bodyweight in the Dex group after administration compared with other groups and the levels of PGE 2 in the plasma were significantly higher than in the WBC-H group, which might be due to the long administration time and the excessive dose of dexamethasone. In the past, the PK characteristics of a single component from TCM in the normal organism were mainly studied, but a growing number of studies have shown that TCM is a complex system, and the pharmacokinetics of a single component cannot characterize its pharmacokinetics in vivo (Li et al, 2014;Wang et al, 2017). Furthermore, the parameters of PK and the concentration of drugs in the blood are influenced by the pathological state, Chinese herbal formulas and other factors Ling et al, 2017 The PK results were calculated by NCA (Chandrasena & Ronald, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that there was a progressive decrease in bodyweight in the Dex group after administration compared with other groups and the levels of PGE 2 in the plasma were significantly higher than in the WBC-H group, which might be due to the long administration time and the excessive dose of dexamethasone. In the past, the PK characteristics of a single component from TCM in the normal organism were mainly studied, but a growing number of studies have shown that TCM is a complex system, and the pharmacokinetics of a single component cannot characterize its pharmacokinetics in vivo (Li et al, 2014;Wang et al, 2017). Furthermore, the parameters of PK and the concentration of drugs in the blood are influenced by the pathological state, Chinese herbal formulas and other factors Ling et al, 2017 The PK results were calculated by NCA (Chandrasena & Ronald, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was proved that fraxetin- O -glucuronides are not transported via the canalicular transporter BCRP (Figure 8). Therefore, the elucidation of transporter MRP2’s involvement in the excretion of fraxetin- O -glucuronides would help to understand the biliary clearance of fraxetin, which may also better explain the pharmacokinetics of fraxetin (Wang H. et al, 2016; Wang et al, 2017). Recently, a newly developed MDCKII-MRP2-UGT1A1 cell model was extensively employed to characterize how overexpression of MRP2 and UGT1A1 affects the cellular kinetics of a flavonoid glucuronidation processes (Wang M. et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The maximal plasma concentration and half-life of fraxetin are 2250 ng/mL (∼11 μM) and 11 h after oral administration of fraxin (50 mg/kg) in rats, respectively (Wang H. et al, 2016). In addition, fraxetin has pharmacokinetic parameters similar to those of fraxin after treatment of rodents with Cortex Fraxini extracts (including 60 mg/kg fraxin and 40 mg/kg fraxetin) (Wang et al, 2017). In contrast to the hydrolysis reaction in rodents, a novel enzyme named scopoletin 8-hydroxylase catalyzes hydroxylation at the C-8 position of scopoletin, leading to fraxetin production in plants (Siwinska et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The preclinical pharmacokinetic studies of most drugs are conducted in healthy animals, and their properties in healthy animals can indeed be used to make critical decisions supporting the efficacy and safety of the drugs [46]. However, the presence of a pathological status could seriously affect drug absorption, distribution, metabolism, and excretion (ADME), which are directly related to both the drug efficacy and the severity of the side effects [47][48][49]. Therefore, for clinical application, it is more important to study the pharmacokinetic process of drug disposition using animal models corresponding to human diseases, rather than healthy animal models.…”
Section: Discussionmentioning
confidence: 99%